2023
DOI: 10.3389/fcimb.2023.1103957
|View full text |Cite
|
Sign up to set email alerts
|

4-Allyl-2-methoxyphenol modulates the expression of genes involved in efflux pump, biofilm formation and sterol biosynthesis in azole resistant Aspergillus fumigatus

Abstract: IntroductionAntifungal therapy for aspergillosis is becoming problematic because of the toxicity of currently available drugs, biofilm formation on host surface, and increasing prevalence of azole resistance in Aspergillus fumigatus. Plants are rich source of bioactive molecules and antimicrobial activity of aromatic bioactive compounds draws attention because of its promising biological properties. The present study elucidated the antibiofilm activity of 4-allyl-2-methoxyphenol (eugenol) against azole-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…4-allyl-2-methoxyphenol (eugenol) is a natural phenolic bioactive component extracted from clove oil, nutmeg, and basil ( Ferreira et al, 2017 ). Sen et al (2023) investigated the impact of eugenol on inhibiting efflux pumps and biofilm formation in 10 azole-resistant Aspergillus fumigatus (ARAF) isolates collected from 245 Aspergillus environmental samples. The confocal laser scanning microscopy results showed that the eugenol treatment caused a loss of extracellular matrix of ARAF biofilm.…”
Section: The Effects Of Epis On Biofilm Formationmentioning
confidence: 99%
“…4-allyl-2-methoxyphenol (eugenol) is a natural phenolic bioactive component extracted from clove oil, nutmeg, and basil ( Ferreira et al, 2017 ). Sen et al (2023) investigated the impact of eugenol on inhibiting efflux pumps and biofilm formation in 10 azole-resistant Aspergillus fumigatus (ARAF) isolates collected from 245 Aspergillus environmental samples. The confocal laser scanning microscopy results showed that the eugenol treatment caused a loss of extracellular matrix of ARAF biofilm.…”
Section: The Effects Of Epis On Biofilm Formationmentioning
confidence: 99%